The Potential of Roselle Calyx Extract Gel as a Disclosing Agent for Detecting Dental Plaque - Riana Syauqi, Anindia; Suwandi, Trijani (Jurnal Kedokteran Gigi Terpadu, 2025)
Bacterial plaque is a common source of dental and oral health problems such as caries  and periodontal diseases. Tooth brushing, flossing, usage of interdental brush, and rinsing with antiseptic are solutions for removing bacterial plaque. Bacterial plaque on the surface of the teeth cannot be seen directly, so the usage of a supporting tool, namely a disclosing agent is needed to visualize the presence of bacterial plaque. A disclosing agent can be in the form of a gel, solution, or chewable tablet. Production of disclosing agents using synthetic dyes like erythrosine has many drawbacks. An alternative natural ingredient that can be used as a substitute is dye made from rosella flower petals. The petals have a natural red-colored pigment that comes from anthocyanin compounds and can be obtained through extraction using the maceration process. The extract is formulated into a gel to optimize its effectiveness. Gel has more advantages compared to other forms disclosing agents in terms of shelf life. Physical stability test of gel made with rosella flower petals extract is needed to observe its longevity during storage. Through this literature review, it was concluded that natural coloring compounds found in rosella flower petals have potential to be used as a disclosing agent in identifying bacterial plaque.